Maximized pseudo-graphitic content in self-supported hollow interconnected carbon foam boosting ultrastable Na-ion storage. (1st March 2021) - Ye, Xinli; Wang, Haisheng; Chen, Zhaofeng; Li, Min; Wang, Ting; Wu, Cao; Zhang, Junxiong; Shen, Ze Xiang
Abstract: Hard carbons are the most promising commercialized anodes for sodium-ion batteries (SIBs). However, it is still a great challenge to design highly stable hard carbon anodes coupled with a large reversible capacity. Herein, a self-supported hollow interconnected carbon foam (HICF) is developed by one-step pyrolysis of a commercial and low-cost melamine sponge. The integration of interconnected network and hollow feature can not only provide strong mechanical stability and additional inner space to effectively accommodate the structural deformation from Na + insertion/extraction, but also enable fast electron and Na-ion transport to achieve a large reversible capacity. As a result, HICF delivers a large reversible capacity of 306 mAh g −1 at 100 mA g −1 and an ultralong cycle life with 86.4% capacity retention over 1000 cycles at 1000 mA g −1 . The superior Na-storage performance is also contributed by the maximized content (63.24%) of pseudo-graphitic phase in HICF realized by tuning pyrolysis time, as the pseudo-graphitic phase could store more sodium ions and maintain more stable microstructure owing to its appropriate d -spacing than highly disordered phase. Furthermore, kinetic analysis based on cyclic voltammetry (CV) and galvanostatic intermittent titration technique (GITT) verifies the adsorption–intercalation mechanism. This work provides a low-cost and high-performance anode candidate for the future practical applications of SIBs.